The Cryptographic Shield: How Advanced Encryption Secures Health Data in AI Systems - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into healthcare promises a revolution in diagnostics, personalized medicine, and operational efficiency. Howeve...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care